2022
DOI: 10.1177/03635465221079844
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Athletes with Femoroacetabular Impingement and Painful Internal Snapping Treated Arthroscopically with Intrabursal Iliopsoas Fractional Lengthening: High Rate of Return to Sport and Favorable Midterm Functional Outcomes

Abstract: Background: Athletes with femoroacetabular impingement syndrome (FAIS) who undergo hip arthroscopy with iliopsoas fractional lengthening (IFL) in the context of painful internal snapping have demonstrated favorable patient–reported outcomes (PROs), return to sport (RTS), and resolution of internal snapping symptoms at short term follow–up. Midterm outcomes have not been established. Purposes: (1) To report minimum 5–year PROs and RTS rate in competitive athletes who underwent primary hip arthroscopy for FAIS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…and Perets et al . evaluate the use of IFL and the impact on return to sport [ 5 , 6 ]. In the Jimenez et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Perets et al . evaluate the use of IFL and the impact on return to sport [ 5 , 6 ]. In the Jimenez et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the Jimenez et al . study, athletes with FAI and painful ISHS were identified as a specific patient population that could benefit from intrabursal IFL [ 5 ]. The study found that this treatment approach was effective for managing hip pain in these athletes, allowing them to return to their pre-injury level of sport and achieve favorable functional outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Patients completed the majority of surveys while in clinic or via electronic database platforms, although some were collected via a telephone interview as has been performed previously. 21,33,43 Clinically significant outcomes including MCID and PASS were calculated using previously published thresholds for arthroscopic labral repair at 5-year follow-up including the HOS-SS (MCID, 15.2; PASS, 80.9), HOS-ADL (MCID, 10.2; PASS, 92.2), mHHS (MCID, 11.4; PASS, 83.6), and iHOT-12 (MCID, 15.1; PASS, 74.3). 39 The secondary outcome measure was RTS rate and duration.…”
Section: Evaluation Of Functional Outcomesmentioning
confidence: 99%
“…38,46,63 Although recent studies have established favorable outcomes in athletes at midterm follow-up, to our best knowledge, there are no studies that have evaluated sex-based differences in the presentation and outcomes of these athletes. 25,33,43,57,58 The purpose of this study was (1) to report minimum 5year patient-reported outcome (PRO) scores as well as RTS and continuation of sport (CTS) rates for elite female athletes undergoing hip arthroscopic surgery for FAIS and (2) to compare clinical results with those of a matched control group of elite male athletes. It was hypothesized that elite female athletes would achieve favorable outcomes at midterm follow-up and that these outcomes would be similar to those of a control group of elite male athletes.…”
mentioning
confidence: 99%
“…38,46,63 Although recent studies have established favorable outcomes in athletes at midterm follow-up, to our best knowledge, there are no studies that have evaluated sex-based differences in the presentation and outcomes of these athletes. 25,33,43,57,58…”
mentioning
confidence: 99%